Method of Extraction of Lead from Copper alloys-With a focus on Brass and Bronze Recycled Materials - Chandrasekaran,Deepak Ram; Basaligundi,Manish Basavaraj (2021)
With recent developments and advancements of technology in the 21st century, the copper industry faces challenges in lowering the lead content in copper alloy scraps due to stricter regulation for the usage of lead. Lead is added to brass and bronze to increase the machinability and to reduce wear. Lead is a significant concern to the environment, and it is categorized as a hazardous material. Lead removal is a critical way to tackle the situation of recycled copper alloy scraps to meet the current regulations. This study accumulates knowledge of all possible lead separation methods and tests two particular method, i.e., Compound separation using Ca-Si2 and solidification of brass and bronze by slow cooling, to investigate the behaviour of lead and other alloying elements during slow cooling and Ca-Si2 compound addition at high temperatures. The sample was prepared by melting 100 g of brass and bronze chip at 1050 oC along with the Ca-Si2 for 35 minutes. Then it was removed from the furnace and allowed to solidify at room temperature. They are cut into a small 1- 1.5 cm cube at the middle part of the melt, packed with epoxy, grind and polished. On quantitative analysis of samples under the scanning electron microscope (SEM), it could be observed that around 20 % of lead is removed from the bronze alloys through compound separation method using Ca-Si2. There was formation of Pb-Ca intermetallic in small globules, which could be observed throughout the matrix upon close examination of the microstructure. By slow cooling of brass and bronze we were able to separate 60 % of lead from the middle part of the melt to the bottom region for brass and 53 % of lead to top part in the bronze.
Keywords: Copper alloys; Lead; Slow cooling; Ca-Si2 Lead separation; Recycling